Unexpected discovery in the thyroid cartilage during voice deepening surgery - Dalia Gustaityte Larsen; Kursat Yelken (Clinical Case Reports, 2023)
Key clinical message Voice deepening surgery has en increasing interest among laryngologist worldwide and a case of surprising foreign body in the thyroid cartilage awakes alert thoughts of awareness to certain patient group.